Zur Frage der natürlichen Dauerhaftigkeit einiger Hölzer aus China gegen Termiten (Isoptera). - Hrdý, Ivan (Contributions to Entomology = Beiträge zur Entomologie, 1961)
1. Samples of the following wood species were tested as to resistance against termites: Fraxinus chinensis, Ternstroemia gymnothera, Machilus sp., Pithecelobium lucidum, Ilex purpurea, Diospyros morrisiana, Pinus massoniana, and Alniphylum fortunei. During experiments in the laboratory, especially with Kalotermes flavicollis and Reticulitermes lucifugus all wood samples were damaged so that none of the above mentioned species may be designated as absolutely resistant against termites. - 2. The test method with R. lucifugus in a small ring immediately on the wood showed results which allow to classify the test samples of Fraxinus chinensis, Machilus sp. and partially also Ternstroemia gymnothera as more resistant. (These wood samples remained without any damage or showed only very slight damages, also when treated by the test method after Schmidt.) These results agree partially with those obtained during a field experiment according to which the samples of Fraxinus chinensis, Ternstroemia gymnothera and Machilus sp. were placed into the group containing wood species which are very little attacked by termites. - 3. For evaluation of wood samples in the laboratory by different methods the test with K. flavicollis in a small glass ring immediately on the wood has proved suitably. A similar method with R. lucifugus stands also the test, but perhaps it will lay less claim to the resistance of the test sample.